The environmental devastation of Ukraine: a result of russia's war crimes - Kharchenko, Viacheslav; Kotynskyy, Andriy; Yakymenko, Igor (My University, 2024)
The Russian full-scale invasion of Ukraine in February 2022 and the ongoing Russian-Ukrainian war have a significant impact on the environment. Russia is waging a war in the manner of war crimes. During the full-scale war, almost 5.3 thousand facts of causing damage to the environment as a result of Russian aggression were documented. Approximate environmental damage are equal to more than 57 billion euros. The scale of environmental crimes of Russian invaders is huge, needs to be stopped immediately and fully compensated by Russian regime.

Повномасштабне вторгнення Росії в Україну в лютому 2022 року та російсько-українська війна, яка триває, мають значний вплив на довкілля. Росія веде війну в манері військових злочинів. За час повномасштабної війни задокументовано майже 5,3 тис. фактів заподіяння шкоди довкіллю внаслідок російської агресії. Орієнтовний збиток навколишньому середовищу становить понад 57 мільярдів євро. Масштаби екологічних злочинів російських загарбників величезні, потребують негайного припинення та повної компенсації російським режимом.
Keywords: environmental devastation of Ukraine; russian invasion; environmental damage; war crimes; середовищчне спустошення України; російське вторгнення; шкода довкіллю; військові злочини; кафедра екології та екоменеджменту